HIGIENE SANITASI DAN ANALISIS ZAT PEMANIS BUATAN PADA DODOL YANG DI PRODUKSI DI KECAMATAN PANYABUNGAN KABUPATEN MANDAILING NATAL TAHUN 2012 - Juita Asnipa; Wirsal Hasan; Taufik Ashar (Lingkungan dan Kesehatan Kerja, 2013)
Hygiene sanitation and analysis of artificial sweeteners on the produce of dodol on Kecamatan Panyabungan Kabupaten Mandailing Natal in 2012. Dodol is a kind of snack which is popular and spread among the Indonesian community. The process which is home industry made the control of sweetener usage is unclear, based on the producer desire. More over the process is still traditionally, as of the workers do not care enough to the hygiene sanitation of the dodol making process. The purpose of this research was to obtain the description of hygiene sanitation process and the analysis of artificial sweeteners content on the produce of dodol snack in Kecamatan Panyabungan Kabupaten Mandailing Natal in 2012. The type of this research was descriptive survey by observing sanitation hygiene and laboratory analysis to obtain artificial sweetener contents on dodol. The result of the research showsed that hygiene sanitation principal on dodol making process which comply with Ministry of Health Decree of Indonesia Number 942 / Menkes / SK / VII/2003 was storage of raw. From the 7 samples of dodol which inspected, there were 3 samples which contain of artificial sweeteners with saccharin grading are 00274 mg/kg, 0.0073 mg/kg, and 0.0054 mg/kg which comply with health permit, according to Permenkes RI No.722/Menkes/Per / IX/1988. The Health Department needs to conduct a thorough counseling and supervision by the related institution (Department of Health) on the importance of food hygiene sanitation, also counseling to the producer in the usage of food sweeteners. Key words: Dodol , Hygiene Sanitation, Artificial Sweeteners.